2013
DOI: 10.1016/j.suronc.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiotherapy in colorectal cancer: Systematic review and meta-analysis of techniques, long-term outcomes, and complications

Abstract: Background The precise contribution of IORT to the management of locally advanced and recurrent colorectal cancer (CRC) remains uncertain. We performed a systematic review and meta-analysis to assess the value of IORT in this setting. Methods Studies published between 1965 and 2011 that reported outcomes after IORT for advanced or recurrent CRC were identified by an electronic literature search. Studies were assessed for methodological quality and design, and evaluated for technique of IORT delivery, oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 70 publications
0
82
1
5
Order By: Relevance
“…Postoperative mortality associated with the use of IORT ranges from 0 to 3.6%, irrespective of the IORT used [10,23,32]. In the literature, 3-month postoperative mortality rates range from 0% to 8% [4,26,28,29,37,39]. In the present study, two postoperative deaths were reported (2.5%); however, none of them was attributed to the use of IORT.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Postoperative mortality associated with the use of IORT ranges from 0 to 3.6%, irrespective of the IORT used [10,23,32]. In the literature, 3-month postoperative mortality rates range from 0% to 8% [4,26,28,29,37,39]. In the present study, two postoperative deaths were reported (2.5%); however, none of them was attributed to the use of IORT.…”
Section: Discussioncontrasting
confidence: 41%
“…Although the use of IORT as a component of combined multimodal therapy may increase the survival by improving the local control, there are no randomized trials on IORT in CRC [9,25]. Meta-analysis of the non-randomized reports in the treatment of recurrent CRC showed improved 5-year overall survival after IORT [29]. Moreover, better local control with a lower risk of relapse at higher doses of radiation have been reported with the use of IORT [5,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International guidelines recommend prescription to the 90% isodose for adequate tumour coverage, but give no indications of acceptable uncertainties. 6 Treatment outcomes have been assessed in several studies, 7,8 but cannot be correlated with patient-specific dose distributions. In this context, it is necessary to first determine how frequently step-like surfaces occur in clinical practice and how great is the effect of clinically occurring irregularities on the dose distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Большинство авторов, описывающих собственный опыт проведения АСР при раке прямой кишки (РПК), указывают, что их пациенты получали те или иные варианты предоперационной и/или интраоперацион-ной лучевой терапии (ЛТ), однако ее режимы часто разнятся [7][8][9].…”
Section: However the Choice Of Tactics For This Patient Category Remunclassified